Solution blow-spun polyacrylonitrile–polyamide thin-film nanofibrous composite membrane for the removal of fermentation inhibitors - Glebert C. Dadol; Leonard D. Tijing; Ramelito C. Agapay; Camila Flor Y. Lobarbio; Noel Peter B. Tan (Nanocomposites)
This study aims to develop a thin-film nanofibrous composite (TFNC) membrane for removing fermentation inhibitors from a hydrolysate solution. Such membrane was fabricated via interfacial polymerization of a polyamide thin-film layer on top of a solution blow-spun polyacrylonitrile nanofiber scaffold. The effects of pH (3.29, 4.29, 8.26) and pressure (4, 6.67, 9.33, 12 bar) on the membrane’s performance were investigated. The TFNC membrane had a high pure water permeability of 21.06 L/m2-h-bar and was able to deliver satisfactory rejection coefficients at pH 3.29 and pressure of 4 bar (glucose − 91.84%, xylose − 86.06%, hydroxymethylfurfural − 20.52%, furfural − 21.32%). Different pH settings resulted in similar permeate fluxes, but increasing the pH from acidic to basic reduced the rejection coefficients due to electrostatic repulsion. Increasing the pressure increased the permeate flux but decreased the rejection coefficients. The developed membrane showed remarkable permeability and effectively removed inhibitors, useful in biorefineries.